2017
DOI: 10.1007/s11182-017-1005-y
|View full text |Cite
|
Sign up to set email alerts
|

Lasing of a Solid-State Active Element Based on Anodized Aluminum Oxide Film Doped with Rhodamine 6G

Abstract: Spectral-luminescent and lasing characteristics of rhodamine 6G in porous aluminum oxide films anodized under various conditions are investigated. Lasing is obtained without external resonator in the longitudinal scheme under excitation by the second harmonic of Nd 3+ :YAG-laser radiation. The threshold pump power densities are in the range 3.5-15 MW/cm 2 depending on the anodizing conditions. Wherein, the lasing line narrows down from 12 to 5 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…2D NAA-PCs in the form of slabs developed by Masuda and Yokoyama achieved outstandingly high-quality factors, with values of ∼6838 and ∼6333, respectively. Although 1D NAA-GIFs achieve lasing qualities 1 order of magnitude lower, these PCs provide higher lasing quality than that reported for other 2D NAA-based organic solid-state incoherent random lasing systems, with maximum Q LE and G LE values of ∼125 and ∼10.4, respectively, and a maximum Q LE · G LE value of ∼536. Unfortunately, lasing emissions from 1D NAA-DBRs developed by Yang and co-workers were not characterized and thus a comparison with that study is not possible .…”
Section: Results and Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…2D NAA-PCs in the form of slabs developed by Masuda and Yokoyama achieved outstandingly high-quality factors, with values of ∼6838 and ∼6333, respectively. Although 1D NAA-GIFs achieve lasing qualities 1 order of magnitude lower, these PCs provide higher lasing quality than that reported for other 2D NAA-based organic solid-state incoherent random lasing systems, with maximum Q LE and G LE values of ∼125 and ∼10.4, respectively, and a maximum Q LE · G LE value of ∼536. Unfortunately, lasing emissions from 1D NAA-DBRs developed by Yang and co-workers were not characterized and thus a comparison with that study is not possible .…”
Section: Results and Discussionmentioning
confidence: 59%
“…An alternative approach to overcome this limitation is functionalizing the inner surface of NAA-PCs with layers of light-emitting materials . Masuda and co-workers realized the first organic solid-state lasing systems from model 2D NAA-PC slabs by modifying their inner surface with composite gain medium layers of fluorophores and dendrimersbranched polymeric molecules. These organic solid-state PC structures yield lasing emissions (LEs) with subnanometric bandwidth (i.e., ∼0.08 nm) and giant quality factor (i.e., ∼6330). However, demonstrations of lasing emissions from NAA-based PC structures are still limited to a few studies. 2D NAA-PC lasing systems suffer from two main constraints: (i) coupling and collection of light at the cross section of thin slabs are challenging and (ii) a constrained range of pore diameter and interpore distance within self-organized regimes. In contrast to their 2D counterparts, 1D NAA-PCs would provide more flexible platforms to develop solid-state lasing systems since (i) the range of lattice constant (period length) can be engineered with precision across the broad spectrum from UV to IR (ii) and more forms of NAA-based PC architectures can be realized (e.g., microcavities, DBRs, GIFs, BSBRs) to harness distinct types of light–matter interactions (e.g., light confinement and recirculation, slow light, hybrid plasmonic–photonic modes).…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies by Masuda and co-workers demonstrated slow photon-based organic–inorganic solid-state lasing systems using model 2D NAA slabs functionalized with fluorophores and dendrimers. The PSB of 2D NAA photonic crystals can enhance spontaneous emission by increasing the radiative rate of the gain medium (i.e., fluorophore molecules) through alteration of the dispersion or density of states of emitted photons at the red edge of the PSB (i.e., dielectric component of the porous photonic crystal). Although slow photon lasers based on NAA slabs showed outstanding quality factors (i.e., ∼6330) and ultranarrow bandwidths (i.e., ∼0.08 nm), coupling excitation and the collection of emitted light at the cross section of these thin slabs is challenging. Alternative approaches have focused on the development of distinct forms of RLs combining NAA and organic fluorophores. In these systems, the characteristics of lasing can be engineered in a cavity-free structure by tuning the density of states of the electromagnetic emission through the structural engineering of nanopores (scattering centers). NAA-based RLs (NAA-RLs) also provide operational simplicity because optical excitation and the collection of emitted light can be performed perpendicularly to the cross section of the NAA thin film.…”
Section: Introductionmentioning
confidence: 99%